2000
DOI: 10.1128/iai.68.6.3772-3775.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Functional cra Gene Is Required for Salmonella enterica Serovar Typhimurium Virulence in BALB/c Mice

Abstract: A minitransposon mutant of Salmonella enterica serovar Typhimurium SR-11, SR-11 Fad−, is unable to utilize gluconeogenic substrates as carbon sources and is avirulent and immunogenic when administered perorally to BALB/c mice (M. J. Utley et al., FEMS Microbiol. Lett., 163:129–134, 1998). Here, evidence is presented that the mutation in SR-11 Fad− that renders the strain avirulent is in the cra gene, which encodes the Cra protein, a regulator of central carbon metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The Cra protein was initially characterized as the fructose repressor FruR and was demonstrated to be a global regulatory protein in carbohydrate metabolism (Saier & Ramseier, 1996). Although it has been shown that Cra regulates numerous genes involved in carbohydrate metabolism (Saier & Ramseier, 1996; Sarkar et al , 2008), growth rate (Ow et al , 2007) and bacterial virulence (Allen et al , 2000), there is no report showing the role of Cra in acid survival. And here, we also detected the decreased expression of cra at acidic pH (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The Cra protein was initially characterized as the fructose repressor FruR and was demonstrated to be a global regulatory protein in carbohydrate metabolism (Saier & Ramseier, 1996). Although it has been shown that Cra regulates numerous genes involved in carbohydrate metabolism (Saier & Ramseier, 1996; Sarkar et al , 2008), growth rate (Ow et al , 2007) and bacterial virulence (Allen et al , 2000), there is no report showing the role of Cra in acid survival. And here, we also detected the decreased expression of cra at acidic pH (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cra has been reported to be an activator of virulence in both Salmonella (22) and EHEC (34). We previously reported on Cra's ability to activate Ler, the master regulator of the LEE genes, and consequently the transcription and translation of genes in this PI (34).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the fact that Cra and KdpE not only regulate virulence factors (22,23,34) but also are involved in carbon metabolism regulation (15)(16)(17)44), we investigated whether these regulators affected EHEC growth rates. In particular, we wanted to examine differences during growth in low-glucose DMEM, conditions that have been shown to be optimal for LEE gene expression and AE lesion formation in vitro (45,46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catabolism of C2 substrates such as fatty acids also appears to play a role in Salmonella metabolism in vivo , because mutants of S. typhimurium that cannot grow on C2 substrates in vitro are attenuated in mice (Utley et al ., 1998). Moreover, gene products required for normal growth and/or persistence in vivo include malic enzyme (Valentine et al ., 1998), isocitrate lyase (Fang et al ., 2005) and catabolite repressor/activator (Cra) (Allen et al ., 2000), which upregulates expression of key enzymes in the glyoxylate and gluconeogenesis pathways (Saier and Ramseier, 1996) (Figs 1 and 3). Interestingly, isocitrate lyase appears to be dispensable for acute lethal infection in genetically susceptible mice but essential for persistence in a mouse model of chronic infection (Fang et al ., 2005).…”
Section: Salmonellaementioning
confidence: 99%